OLEANOLIC ACID, A PROSPECTIVE PROTECTIVE AGENT AGAINST BRAIN ENERGY METABOLISM AND OXIDATIVE DYSFUNCTIONS FOLLOWING HEXAVALENT CHROMIUM EXPOSURE IN MICE - PAL, SUDIPTA (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: Effect of oleanolic acid against hexavalent chromium-induced altered brain energy metabolism associated with oxidative stress was evaluated in the present study. Methods: Swiss albino mice were divided into three groups, Control (n=6), chromium-treated (n=6), and oleanolic acid (OA) supplemented (n=6). The chromium treated group was orally administered with K2Cr2O7 for 30 days at a dose of 10 mg/kg b.w/day. OA supplementation was given at a dose of 5 mg/kg bw/day for the past 14 days of chromium treatment. Control group received the vehicle only. After the treatment, whole brain was removed for examining the parameters such as pyruvic acid, free amino nitrogen, tissue protein, TCA cycle enzyme activities, NADH dehydrogenase function, and oxidative stress markers. Results: Significant decrease in cerebral pyruvic acid content associated with suppressed malate dehydrogenase and succinate dehydrogenase activities were observed. The NADH dehydrogenase activity was inhibited owing to enhanced accumulation of chromium in cerebral tissue. Depletion of proteins and increased free amino acid nitrogen were accompanied with inhibited cathepsin, pronase and trypsin activities, and increased transaminase function. In addition, GSH content was decreased along with increased lipid peroxidation, oxidized GSSG content, TG/GSSG ratio, carbonylated protein content, and tissue free hydroxyl radical formation. Superoxide dismutase, catalase, glutathione reductase, and glutathione peroxidase were also inhibited by hexavalent chromium. Oleanolic acid supplementation was found to have significant protective effect against brain metabolic and oxidative dysfunctions. Conclusion: The present study elucidated therapeutic efficacy of oleanolic acid against hexavalent chromium toxicity in brain tissue of mice.